2015
DOI: 10.1039/c5nr02616d
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and carrier transport in doped Si/SiO2quantum dots

Abstract: In the present theoretical work we have considered impurities, either boron or phosphorous, located at different substitutional sites in silicon quantum dots (Si-QDs) with diameters around 1.5 nm, embedded in a SiO2 matrix. Formation energy calculations reveal that the most energetically-favored doping sites are inside the QD and at the Si/SiO2 interface for P and B impurities, respectively. Furthermore, electron and hole transport calculations show in all the cases a strong reduction of the minimum voltage th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 72 publications
(124 reference statements)
7
21
0
Order By: Relevance
“…It is worth noting that this experimental observation of a B aggregation at the Si‐nc/SiO 2 interface is consistent with theoretical computation lead on B‐doped Si‐ncs embedded in SiO 2 . Moreover, it confirms the recent experimental investigation of Hiller et al based on a PECVD elaboration .…”
supporting
confidence: 91%
“…It is worth noting that this experimental observation of a B aggregation at the Si‐nc/SiO 2 interface is consistent with theoretical computation lead on B‐doped Si‐ncs embedded in SiO 2 . Moreover, it confirms the recent experimental investigation of Hiller et al based on a PECVD elaboration .…”
supporting
confidence: 91%
“…Realistic calculations for Si-NCs embedded in a solid matrix were performed by Guerra et al [166,222]. SiO 2 -embedded Si-NCs were generated starting from a 3x3x3 β-cristobalite-SiO 2 matrix (for a total of 648 atoms), by removing all the O atoms inside a sphere whose radius determines the Si-NC size.…”
Section: Ab-initio Calculations Formation Energies and Electronic Prmentioning
confidence: 99%
“…They found that B atoms prefer to stay immediately below the Si/SiO 2 interface, whereas P atoms are preferentially located in the Si‐NC core. Ab initio calculations for doped Si‐NCs clearly embedded in a SiO 2 matrix were performed by Guerra et al The SiO 2 ‐embedded Si‐NCs have been generated starting from a large SiO 2 matrix and removing all the O atoms inside a sphere whose radius determines the Si‐NC size. After the ionic relaxation, the Si/SiO 2 interface forms stressed bonds, while far from the interface the bulk atomic densities are recovered .…”
Section: Matrix Embedded Si‐ncsmentioning
confidence: 99%